How far does a big push really push? Long-term effects of an asset transfer program on employment trajectories - Misha, Farzana A.; Raza, Wameq A.; Ara, Jinnat; de Poel, Ellen van (University of Chicago Press Journals, 2022)
This article was published in The Economic Development and Cultural Change [©2019 Published by The University of Chicago. All rights reserved.] and the definite version is available at: https://doi.org/10.1086/700556 The Article's website is at: https://www.journals.uchicago.edu/doi/abs/10.1086/700556?journalCode=edcc